Breaking Barriers: Investigating the Effects of 100% Foreign Ownership on Business Entry in Dubai - Ahmed Rashad (ZBW – Leibniz Information Centre for Economics, 2023)
The regulatory and institutional environment of a nation plays a critical role in shaping the level of entrepreneurship. By creating a conducive regulatory and institutional environment, governments can encourage entrepreneurial activity, leading to job creation, innovation, and economic growth. The United Arab Emirates has recently deregulated the ownership rules for more than 1,000 commercial and industrial activities, allowing full ownership of commercial companies in the UAE without requiring a partnership with a national sponsor. Before the introduction of these amendments, foreign ownership was not permitted to exceed 49% of the total assets of a company outside the free zones, with the majority stake being held by an Emirati partner. This study represents the first attempt to assess the short-term impact of the liberalization of business ownership rules on the number of newly registered firms in the UAE. The study collects unique data that covers all types of business activity in Dubai, using monthly data on the number of newly issued business licenses. We developed a difference-in-difference model with a treatment and a control group using panel data regression models. Our findings suggest that the liberalization of the ownership rules has led to a significant surge in the number of new business licenses in the sectors impacted by the liberalization policy. This early evidence suggests that relaxing the restrictions on business ownership may stimulate entrepreneurial activity and business creation in the Gulf region.
Keywords: G18; G38; L51; M13; 330; New Firms; Gulf region; regulatory reform; entrepreneurship